2022
DOI: 10.1017/jfm.2022.407
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effects of particle near-wall motions on turbulence statistics in particle-laden flows

Abstract: Experiments on particle-free and particle-laden flows with the same incoming velocity were conducted in a horizontal wind tunnel. Three cases of particle-laden flows with different degrees of particle near-wall motions and similar particle volume fractions, including top-release particles, local-laying sand beds and global-laying sand beds, were designed to investigate the effects of collision bounces and impact splashing on turbulence statistics. The top-released particles accelerate the fluid during gravitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 79 publications
9
25
0
Order By: Relevance
“…The experiments were carried out in the multifunctional environmental wind tunnel laboratory at Lanzhou University, and the experimental set-up was described in detail by Liu, Feng & Zheng (2022). Therefore, only a brief description is provided in this section.…”
Section: Experimental Settings and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiments were carried out in the multifunctional environmental wind tunnel laboratory at Lanzhou University, and the experimental set-up was described in detail by Liu, Feng & Zheng (2022). Therefore, only a brief description is provided in this section.…”
Section: Experimental Settings and Treatmentmentioning
confidence: 99%
“…In the two-phase flows, size-selected sand particles from the Tengger Desert, with a density ρ p = 2600 kg m −3 and diameter d p = 203 ± 95 μm (mean ± standard deviation) are used in this study. The particle diameter ranges from 30 to 480 μm and the particle size distribution can be found in Liu et al (2022). Here, we calculate the particle parameters using the average size of the particles (Zheng et al 2021;Zhu et al 2021;Liu et al 2022).…”
Section: Experimental Settings and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of the authors’ knowledge, this is the highest-Reynolds-number particle-laden channel flow case simulated with DNS, presumably due to the rapidly increasing computational cost with higher Reynolds numbers. Liu, Feng & Zheng (2022) experimentally investigated the effects of collision bounces and impact splashing on turbulence statistics in an open-loop wind tunnel at with multiple modes of particle introduction (both released from above as well as eroded from below). They found that top-released particles attenuate the Reynolds stress and weaken the VLSMs, whereas bouncing and splashing generate ascending particles that transport the kinetic energy upwards, resulting in more energetic VLSMs.…”
Section: Introductionmentioning
confidence: 99%